Better Students Ask More Questions.
Evaluate the two compostions(fog)x and (hog)(x) find the inverse...
1 Answer | add yours
You need to compose two functions using the following relation, such that:
`(fog)(x) = f(g(x))`
You should notice that the equation of second function `g(x)` replaces the variable x, in equation of function `f(x)` .
You may consider the following simple example, such that:
`f(x) = 3x - sin x`
`g(x) = sqrt x`
Using the equation `(fog)(x) = f(g(x))` , you can find the result of composition of function `f(x)` and `g(x)` , such that:
`f(g(x)) = 3g(x) - sin (g(x))`
Replacing `sqrt x` for `g(x)` yields:
`f(g(x)) = 3sqrt x - sin (sqrt x` )
Hence, you may evaluate the composition of any two functions, `f(x)` and `g(x)` , using the relation `(fog)(x) = f(g(x)).`
Posted by sciencesolve on June 2, 2013 at 12:56 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.